Drug‐facilitated sexual assault in Africa: A scoping review of empirical evidence - Amzat, Jimoh; Kanmodi, Kehinde Kazeem; Aminu, Kafayat; Egbedina, Eyinade Adeduntan (Public health challenges, 2023)
Sexual assault has been a major social problem worldwide. Drug-facilitated sexual assault (DFSA) is a form of sexual assault facilitated by psychoactive substances. DFSA is highly prevalent worldwide, though it is usually underreported. To understand the situation of DFSA in Africa, there is a need to map the available empirical evidence on DFSA in Africa. Hence, this scoping review was conducted to summarize the existing empirical knowledge and gaps in the literature and inform future research on DFSA in Africa. This study adopted the design by the Arksey and O'Malley's guideline for scoping reviews. Without year limiters, literatures were retrieved through a systematic search of the 11 electronic databases using appropriate search terms and Boolean operators. The retrieved literatures were deduplicated and screened, using Rayyan, to identify eligible literature for inclusion into the review. Only those articles that met the eligibility criteria were included for data charting, collation, and summarization. Four articles were included in this review. Four articles were included in this review. The studies reported the characteristics of offenders and the context in which DFSA occurred. In the reviewed studies, rape of men was only reported among South Africans. Sedatives and alcohol are the most reported substances used in such rape. Perceptions of date rape, as documented by sexual assault survivors, suggest the pervasiveness of victim blaming. Typical DFSA cases appear opportunistic in nature, and an acquaintance is often the culprit. However, disaggregating DFSA as a specific sexual assault requires some logistics, including forensic and toxicological investigations. DFSA is a significant dimension of gender-based sexual violence. Infrastructure development should be improved to support systematic toxicological analyses and services to investigate and understand DFSA.